Management education within a cultural confluence : Twinning programmes in Malaysia - McDonald, Paul; Pratt, Graham (Universiti Utara Malaysia, 1997)
In its steady advance toward Vision 2020, Malaysia has been working hard to balance the skills and competencies of its people commensurate with its economic growth. To this end, educational twinning programmes abound in Malaysia. At present, these programmes are inevitably reliant to a considerable degree on Western thought and science. This paper, written from the perspective of two twinning programme directors, examines cross-cultural management issues underlying educational programme design and delivery. Its focus concentrates on the execution of commerce and business programmes.